U.S. FOREIGN LANGUAGES EDUCATION: MULTICULTURAL PRINCIPLES - Ірина Білецька (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article examines different approaches to the interpretation of the term "multicultural education" and substantiates the author's vision of this category. Major multicultural principles of foreign language education at secondary schools in the United States have been singled out, namely: effective language education policy directly determined at the national, regional and local levels; the formation of a new paradigm of education in foreign languages, rethinking the functions of a foreign language; upgrade of content of foreign language school education, development of their own policies of multicultural education by a school district and the specific institution, integration of bilingual education.